2021
DOI: 10.1186/s12970-021-00459-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 30 days of ketogenic diet on body composition, muscle strength, muscle area, metabolism, and performance in semi-professional soccer players

Abstract: Background A ketogenic diet (KD) is a nutritional approach, usually adopted for weight loss, that restricts daily carbohydrates under 30 g/day. KD showed contradictory results on sport performance, whilst no data are available on team sports. We sought to investigate the influence of a KD on different parameters in semi-professional soccer players. Methods Subjects were randomly assigned to a iso-protein (1.8 g/Kg body weight/day) ketogenic diet (K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 72 publications
2
47
0
Order By: Relevance
“…A more detailed description of the experimental study and physiological measures can be found ( 13 ). Sixteen semi-professional soccer players (25.5 ± 2.8 years, 77.2 ± 11.88 kg) were recruited for the study.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…A more detailed description of the experimental study and physiological measures can be found ( 13 ). Sixteen semi-professional soccer players (25.5 ± 2.8 years, 77.2 ± 11.88 kg) were recruited for the study.…”
Section: Methodsmentioning
confidence: 99%
“…The exclusion criteria were: participants with a body fat percentage over 32%, (determined via dual energy X-ray absorptiometry DXA), cardiovascular, respiratory, gastrointestinal, thyroid or any other metabolic diseases, weight change ± 2 Kg over the last month, adherence to special diets, use of nutritional supplements (except a daily multivitamin-mineral), use of antibiotics ( 17 ), use of medication to control blood lipids or glucose. The anthropometric details of the subjects enrolled in the study were provided in our previous published study ( 13 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations